(untitled) (Bangladesh Journal of Microbiology, 2022)
Escherichia coli are a large and diverse group of bacteria found in the environment, foods and intestines of humans and animals. This study was carried out to observe the genotypic variations in E. coli found at different regions in Bangladesh using Amplified Ribosomal DNA Restriction Analysis (ARDRA) of the 16S rDNA and RAPD (Random Amplified Polymorphic DNA). Sewage samples were collected from different medical college hospitals and a total of 118 samples were observed in this study of which 26 were identified as E. coli based on their cultural, biochemical and molecular characteristics. Antibiotic susceptibility test was carried out where most isolates were resistant to Amoxicillin, Rifampicin and Erythromycin; and some were resistant to kanamycin, ceftriaxone, Chloramphenicol and Azithromycin; besides 73% (N=19 out of 26) of the test isolates were multi-drug resistant. Results of Polymerase chain reaction (PCR) showed that none of the isolates carried Stx1, Stx2 and LT gene. Two genotypic groups were found from Amplified Ribosomal DNA Restriction Analysis (ARDRA) by Alu1 restriction enzyme and seven different Random Amplification of Polymorphic DNA (RAPD) patterns were found. After analyzing, it was found that 24 out of 26 isolates showed similarity with Escherichia coli strain NBRC 102203 and the remaining two isolates showed similarity with Escherichia coli strain Mui T5 based on the restriction patterns of ARDRA and sequences of 16S rDNA. From the study, it was concluded that Escherichia coli strain NBRC 102203 was more prevalent than Escherichia coli strain Mui T5 isolated from sewage sample of hospitals from different regions of Bangladesh. Bangladesh J Microbiol, Volume 38, Number 2, December 2021, pp 39-44